The impact of excessive weight gain on hypertension, steroid induced diabetes, and disease parameters in pediatric systemic lupus erythematosus patients - Damar Prasetya; Sumadiono Sumadiono (World Nutrition Journal, 2022)
Systemic inflammation, corticosteroids therapy, and reduced physical activity may predispose the accumulation of body fat in patients with systemic lupus erythematosus (SLE). However, less is known about its impact in children.(1,2) This study aims to explore the impact of excessive weight gain on pediatric SLE patients.